Anticonvulsive effects of the dopamine agonist lisuride maleate after experimental traumatic brain injury - Zweckberger, Klaus; Simunovic, Filip; Kiening, Karl; Unterberg, Andreas; Sakowitz, Oliver (Neuroscience letters, 2010)
Traumatic brain injury is a heterogeneous disease, encompassing a wide range of pathologies. The dopamine agonist lisuride is well established in the therapy of Parkinson's disease. Additionally to its dopaminergic effects it decreases prolactine release, reducing the amount of inflammatory mediators such as TNF-α or Il-6. Lisuride has strong binding affinity to serotonergic and histaminergic receptors on neuronal and glial cells leading to scavenging of highly reactive free radicals. Due to its interaction with dopaminergic D2 and D4 receptors as well as 5-HT-1A receptors, NMDA-receptor signaling and glutamate-mediated excitotoxicity can be modulated beneficially. Despite of these promising neuroprotective effects, experimental data scrutinizing the effects of lisuride after acute brain injury are sparse. We therefore investigated the effect of lisuride after controlled cortical impact injury (CCII) in rats. 70 male Sprague-Dawley rats were randomized to lisuride or to placebo treatment by an initial s.c. loading dose (0.3mg/kg BW) and following continuous application (0.5mg/kg/d) by s.c. implanted osmotic pumps. In three experimental groups we determined (sub)acute neuro-physiological changes after trauma. Mean arterial blood pressure, intracranial pressure, and electrical brain activity were monitored acutely for up to 3h after trauma. Brain edema formation was assessed 24h after CCII. Furthermore, contusion volumes were quantified by magnetic resonance tomography and neurological testing was performed for up to 7 days after injury. Associated with the administration of lisuride there was a significant reduction in duration and number of post-traumatic seizures. Despite of a sustained arterial hypotension following the initial bolus administration in the treatment group, contusion volumes and neurological function tests did not differ significantly in comparison to the control group. Overall, lisuride seems to have significant anticonvulsive effects but seems not to influence secondary brain damage in this experimental model.
Gesehen am 02.11.2023